2015
DOI: 10.1093/ntr/ntv073
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status Confirmation by Proxy: Validation in a Smoking Cessation Trial

Abstract: Introduction: Biochemical confirmation (BC) of self-report is the gold standard of evidence for abstinence in smoking cessation research, but difficulty in obtaining samples may bias estimates of quit rates. Proxy confirmation (PC) has not been validated in cessation trials. We assessed the feasibility and validity of PC in a cessation trial for hospitalized smokers. Methods: We enrolled 402 daily cigarette smokers during a hospital admission. At enrollment, participants provided demographics, smoking history,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Future efforts may consider tobacco registries to track tobacco status and outcomes after interventions. 44,45 The bidirectional eReferral feedback from a quitline can potentially contribute to such tobacco registries by tracking tobacco status at follow-up calls and describing interventions received. Interoperability between tobacco cessation EHR resources may be a model when developing clinical informatics tools, such as an open EHR.…”
Section: Discussionmentioning
confidence: 99%
“…Future efforts may consider tobacco registries to track tobacco status and outcomes after interventions. 44,45 The bidirectional eReferral feedback from a quitline can potentially contribute to such tobacco registries by tracking tobacco status at follow-up calls and describing interventions received. Interoperability between tobacco cessation EHR resources may be a model when developing clinical informatics tools, such as an open EHR.…”
Section: Discussionmentioning
confidence: 99%
“…37–39 A recent analysis of proxy verification in a clinical trial suggests it is no more valid than self-report. 40 To examine the impact of proxy verification, the proportions of patients who verified abstinence via cotinine, CO, and proxy are reported.…”
Section: Methodsmentioning
confidence: 99%
“…Responses were compared with self-reported smoking history completed by the corresponding patient or relative(s). Owing to the unavailability of biochemical measures of smokingdoften used as a gold standard in smoking cessation studies 16 dself-reported cigarette smoking history was treated as "truth." Specificity, sensitivity, and accuracy analyses were performed to compare patient and relative reports with self-reports for the question, "Have you ever smoked cigarettes (more than 100 in your lifetime)?"…”
Section: Discussionmentioning
confidence: 99%